Lung involvement at presentation predicts disease activity and permanent organ damage at 6, 12 and 24 months follow - up in ANCA - associated vasculitis - Hassan, Tidi M (BioMed Central, 2014)
BACKGROUND: Antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis (AAV) may present with pulmonary involvement ranging from mild to life-threatening disease such as diffuse alveolar hemorrhage. There is a paucity of information regarding morbidity outcomes for AAV subjects presenting with lung involvement. This study determines the relationship between disease activity and damage in these subjects using the Birmingham Vasculitis Activity Score v 3 (BVAS 3) and Vasculitis Damage Index (VDI) respectively. RESULTS: 151 patients with AAV were included with 59 presenting initially with pulmonary involvement. The initial BVAS scores recorded at time of diagnosis were positively correlated with the final VDI scores at 24 months (p < 0.0001, rs = 0.5871). No differences between BVAS and VDI scores were seen for both groups, however in the lung-involvement group only, BVAS scores were significantly higher at 6, 12 and 24 months whilst the VDI scores were significantly higher at 12 and 24 months. Subjects presenting with pulmonary involvement had an increased likelihood for cardiovascular (OR 1.31, 95% CI 0.89, 1.54; p = 0.032) and renal (OR 1.32, 95% CI 1.22, 1.39; p = 0.005) involvement. Subjects presenting with lung involvement with granulomatosis with polyangiitis and microscopic polyangiitis had 24-month VDI scores that were significantly higher (p = 0.027, p = 0.045), and more likely to develop pulmonary fibrosis (OR 1.79, 95% CI 1.48, 2.12; p < 0.001). CONCLUSION: AAV subjects with lung involvement at presentation had a higher disease activity and damage scores at 6, 12 and 24 months follow-up representing a considerable burden of disease despite improvement in overall survival due to the introduction of immunosuppressive therapy.